The heritage : Black Athletes, a divided America, and the politics of patriotism - Bryant, Howard, 1968- (Beacon Press, 2018)
"The Heritage is the story of sports post-9/11, once neutral but now embedded with deference toward the military and police, colliding with the political reawakening of the black athlete in post-Ferguson America"--